Sumpa - Herras, Paolo; Sabas, Brent (Quezon City Meganon Comics Publishing House, 2014)
"The bigger the curse, the harder to break. Curses are broken promises. In order to break a curse, one must first fulfill its promise. Half-human, half-elemental Sumpa knows this all too well, because he's promised to break the biggest curse of them all--the curse of his native land. Accompanies by pre-colonial god Aliw, who knows what broken curse and fulfilled promises these two must have."-- Provided by publisher.
FA-3024g donated by Tepai Pascual.
Keywords: Horror comic books, strips, etc. -- Philippines; Comic books, strips, etc. -- Philippines; Graphic novels